Characteristics of Cervical Precancerous Lesions at a Tertiary Hospital in Bali, Indonesia - I Nyoman Gede Budiana; Ida Bagus Rendra Kurniawan Artha (National Cancer Center - Dharmais Cancer Hospital, 2020)
Background: Cervical cancer is one of the biggest women’s health issues in developing countries including Indonesia. This study is aimed to describe the characteristics of cervical precancerous lesions at a tertiary hospital in Bali, Indonesia.Methods: This is a descriptive study using data from the medical records of patients with precancerous cervical lesions who attended the Gynecologic Oncology Outpatient Clinic Sanglah Hospital Denpasar, Bali, Indonesia, from January to December 2017. Results: There were 276 cases (2.88%) of the cervical precancerous lesion during the study period. The majority of cases were diagnosed within the age group of 36-45 years (37.7%), had low education levels (42.7%), obese (53.5%), multiparous (73.9%), had first sexual intercourse at the age of 16-20 years (41.3%), had used IUD as a contraceptive method (41.4%), and had a cytologic diagnosis of atypical squamous cells of undetermined significance (ASC-US) that preceded the histologic diagnosis (43.2%). The most common histologic diagnosis was CIN I (43.1%) and the most common treatment was cryotherapy (56.2%).Conclusions: The majority of cervical precancerous lesion cases were diagnosed among women who were between her third and fourth decade of life, had low education level, were obese, multiparous, had a sexual debut at a younger age, and were IUD users. The majority of cases were low-grade lesions.